Application of Radioactivity in Medicine - Odilovna, Nabiyeva Gulbakhor; Qayumova, Madina Kadirjon; qizi, Xaydarova Odinaxon No‘monjon (American Journal of Biology and Natural Sciences, 2025)
This article covers the areas of application of the phenomenon of radioactivity in medicine. It provides detailed information about the physicochemical properties of radioactive isotopes, their importance in diagnostics and treatment, as well as modern methods of nuclear medicine (PET, SPECT). The possibilities of effective treatment of cancer diseases through methods such as radiotherapy and radioactive iodine treatment are considered. The article also analyzes safety measures when working with radioactive substances and their role in scientific research. The article may be useful for representatives of the medical field, students, and researchers.